Intracoronary Platelet Release in Patients with and without Coronary Artery Disease - Verheugt, F W; Serruys, P W; Vliet, H van; Spijkers, A; Hugenholtz, P G (Thrombosis and Haemostasis, 1983)
Intracoronary platelet release of beta-thromboglobulin (BTG) was measured in 18 patients with a history of chest pain by analysis of aortic and coronary sinus blood samples in rest and during atrial pacing. Eleven proved to have coronary artery disease, while seven had normal coronary arteriograms and served as controls. In both groups no statistically significant transmyocardial gradient of platelet and plasma BTG content was observed under basal conditions, although the aortic plasma BTG levels in the patients (60.4 ± 4.1 ng/ml) were significantly (p <0.05) higher than in the controls (47.5 ± 2.6 ng/ml). However, also during atrial pacing no significant gradient could be demonstrated in the patients nor in the controls. It is concluded, that in stable coronary artery disease measurable intracoronary platelet release does not occur in rest nor atrial pacing and, therefore, does not seem to contribute to the development of exercise-induced myocardial ischaemia.
Keywords: Coronary artery disease; Angina pectoris; Platelet release; Beta; thromboglobulin